Acquisition and interpretation of English articles by L1 Malay and L1 Tamil speakers - V. Jacob, Premala (2018)
The L2 acquisition of the English articles is perceived to be an extremely difficult process for L2 learners especially those whose L1s lack articles. The English language uses articles to encode definiteness and indefiniteness but the Malay and Tamil languages lack articles. Due to the difficulty faced in article acquisition, this research investigates how article-less L1 Malay and L1 Tamil L2 English learners acquire the concept of definiteness in English articles using an article system proposed in the Article Choice Parameter (ACP) by applying the Fluctuation Hypothesis (FH) and examines how they interpret the English definite articles using Wolters’ Semantic Proposal (WSP). The ACP establishes that articles encode a semantic parameter with two values which are definiteness or specificity. The English language has the definiteness setting of this parameter, and languages like Samoan has the specificity setting. The FH leads to the prediction that L2 learners from article-less L1s upon encountering a language that has an article system will fluctuate between the two settings of the ACP. The FH also predicts that L2 English errors of article use should come in two types: overuse of the with specific indefinites and overuse of a with non-specific definites. The respondents in this study are L1 Malay and L1 Tamil L2 English learners and native English speakers. All these respondents were administered a forced choice elicitation task (FET) to examine the ability of the L2 English learners to acquire the English articles and accurately set the definiteness parameter and a picture-based comprehension task (PCT) to investigate how these learners interpret English definite articles. It focused on whether these learners can differentiate between the definite and demonstrative descriptions as proposed in WSP.The empirical data showed that the L2 English learners article choice is not random but demonstrated sensitivity to the definiteness and specificity of the ACP. This is consistent with the predictions of the FH. Also, the performance showed that learners are more target like as the proficiency level increases. The findings from the PCT indicated clear differences in the responses between the native speakers and the L2 learners in both the definite and demonstrative plural condition. The findings in this task indicated the possibility of the interpretation of the definite article by these article-less L1 learners being influenced by L1 transfer from a closely associated category namely the demonstrative. In conclusion this research has highlighted and explained the process of L2 article acquisition and interpretation among both the L1 Malay and L1 Tamil groups of L2 English learners, that learners on the whole draw upon the L2 input, L1-transfer and UG to acquire the target language. This knowledge will also serve as an important pedagogical tool for ESL instructors to plan the L2 input to address the areas in which L1 Malay and L1 Tamil L2 English learners would face difficulties.